Mass Spectrometry-Based Non-Targeted Lipidome Analysis and Extraction of Markers for the Authentication of White and Black Truffle Species and Their Origin Determination - Eva Tejedor-Calvo; Pedro Marco; Markus Fischer; Marina Creydt (Agriculture)
The visual authentication of high-value truffles (Tuber magnatum and Tuber melanosporum) is challenging, as they share similar morphological characteristics with other truffle species that have a lower economic value. This similarity complicates accurate identification and increases the risk of substitution or mislabeling, which can affect both market prices and consumer trust. For this reason, the aim of this study was to apply a non-targeted lipidomic approach using ion mobility spectrometry-mass spectrometry to distinguish between white (T. magnatum, Tuber borchii, and Tuber oligospermum) and black truffle species (T. melanosprum, T. aestivum, T. aestivum var. uncinatum, T. brumale, and T. indicum) and to determine the different geographical origins of the two most valuable truffle species (T. melanosporum and T. magnatum). Among several hundred features, 37 and 57 lipids were identified as marker compounds to distinguish white and black truffle species using MS/MS spectra and collision cross section (CCS) values, respectively. Only a few marker compounds were necessary to recognize the differences between white and black truffles. In particular, ceramides, glycerolipids, and phospholipids proved to be particularly suitable for separating the species. In addition, different metabolite profiles were determined for T. melanosporum and T. magnatum depending on their geographical origin. These findings lay the groundwork for a comprehensive quality control framework for fresh truffles, ensuring authenticity, detecting adulteration, and preserving their premium status.